Structure of Plant Populations in Constructed Wetlands and Their Ability for Water Purification - Junshuang Yu; Ling Xian; Fan Liu (Plants)
In constructed wetlands (CWs) with multiple plant communities, population structure may change over time and these variations may ultimately influence water quality. However, in CWs with multiple plant communities, it is still unclear how population structure may change over time and how these variations ultimately influence water quality. Here, we established a CW featuring multiple plant species within a polder to investigate the variation in plant population structure and wastewater treatment effect for drainage water over the course of one year. Our results showed that the total species decreased from 52 to 36; however, 20 established species with different ecological types (emerged or submerged) remained with the same functional assembly for nutrient absorption, accounting for 94.69% of relative richness at the initial stage and 91.37% at the last state. The Shannon index showed no significant differences among the initial, middle, and last states. Meanwhile, regarding nutrient content, the total phosphorus (TP) concentration decreased by 57.66% at the middle stage and by 56.76% at the last state. Total nitrogen (TN) decreased by 50.86% and 49.30%, respectively. Chemical oxygen demand (COD) decreased by 36.83% and 38.47%, while chlorophyll a (Chla) decreased by 72.36% and 78.54%, respectively. Redundancy analysis (RDA) results indicated that none of the selected environmental variables significantly affected the species community except for conductivity. Our findings suggest that when utilizing multiple species for CWs, it is essential to focus on the well-established species within the plant community. By maintaining these well-established species, water purification in CWs can be sustained.